Designing and Building Project Management Information Systems Web Based Transaction Reports at BRILink Agents - Elin Rosliani; Tedi Budiman; Yopi Nugraha; Widya Astuti (RISTEC : Research in Information Systems and Technology, 2024)
Effective transaction data management is crucial for the operation of BRILink, particularly for agents who act as intermediaries between the bank and customers. This research aims to design and develop a web-based Project Management Information System to efficiently manage transaction reports. The system supports the recording, processing, and presentation of transaction data in a more structured and easily accessible manner for BRILink agents, thereby enhancing operational productivity.The research method includes requirements analysis, system design using Unified Modeling Language (UML), web framework-based implementation, and testing to ensure functionality. The results show that the developed system can improve the efficiency of report management, reduce data input errors, and provide quick and accurate reports. Equipped with data security features and an intuitive interface, this system is expected to support more effective BRILink agent operations and enhance customer service experiences.